Tarzan 2 - Smith, Brian (Hollywood : Walt Disney, 2005)
Before he was King of the Jungle, Tarzan was an awkward young kid just trying to fit in. When one of his missteps puts his family in jeopardy, Tarzan decides they would be better off without him. His thrilling new journey brings him face to face with the mysterious Zugor, the most powerful force in the land. Together, Tarzan and Zugor discover that being different is not a weakness and that friends and family are the greatest strength of all.
Languages : Turkish, English, German.
Region 2.
Subtitles : Turkish, English, German.
Cast: Harrison Chad, Brenda Grate, George Carlin, Brad Garrett, Estelle Harris.
3-6.
K-3.
Keywords: Movie -- animated films